Metodologi Muhaddithin: Suatu Sorotan - Deraman, Fauzi (Jurnal Usuluddin, 2000)
This article tries to give an overall view on the commitment of early muhaddithin and their efforts to preserve the Traditions (Ahadith) of the Prophet. It discusses the methods used by muhaddithin and its development in the history of recording (tadwin) the Ahadith.